Early identification of local infections in central venous catheters for hemodialysis: A systematic review - José Luis Cobo-Sánchez; Ian Blanco-Mavillard; Noelia Mancebo-Salas; Susana Moya-Mier; Faustino González-Menéndez; Cristina Renedo-González; Mercedes Lázaro-Otero; Raquel Pelayo-Alonso; Zulema Gancedo-González; Joan Ernest de Pedro-Gómez (Elsevier, 2023)
Background: The use of central venous catheters (CVC) is associated with higher morbidity and mortality, related to infectious complications, contributing to poorer clinical outcomes and increased healthcare costs. According to the literature, the incidence of local infections related to CVC for hemodialysis is highly variable. This variability is related to differences in definitions of catheter-related infections. Objective: To identify signs and symptoms for determining local infections (exit site and tunnel tract infections) used in the literature in tunnelled and nontunnelled CVC for hemodialysis. Design: Systematic review Methods: Structured electronic searches were conducted in five electronic databases, from 1 January 2000-31 August 2022, using key words and specific vocabulary, as well as manual searches in several journals. Additionally, vascular access clinical guidelines and infection control clinical guidelines were reviewed. Results: After validity analysis, we selected 40 studies and seven clinical guidelines. The definitions of exit site infection and tunnel infection used in the different studies were heterogeneous. Among the studies, seven (17,5 %) used the definitions of exit site and tunnel infection based on a clinical practice guideline. Three of the studies (7.5 %) used the Twardowski scale definition of exit site infection or a modification. The remaining 30 studies (75 %) used different combinations of signs and symptoms. Conclusions: Definitions of local CVC infections are highly heterogeneous in the revised literature. It is necessary to establish a consensus regarding the definitions of hemodialysis CVC exit site and tunnel infections. Registration: PROSPERO (CRD42022351097).